Transcranial direct current stimulation reconstructs diminished thalamocortical connectivity during prolonged resting wakefulness: a resting-state fMRI pilot study. - Dalong, Guo; Jiyuan, Li; Ying, Zhang; Lei, Zha; Yanhong, Hou; Yongcong, Shao (Brain Imaging & Behavior, 2020)
Reductions in the alertness and information processing capacity of individuals due to sleep deprivation (SD) were previously thought to be related to dysfunction of the thalamocortical network. Previous studies have shown that transcranial direct current stimulation (tDCS) can restore vigilance and information processing after SD. However, the underlying neural mechanisms of this phenomenon remain unclear. The purpose of this study was to investigate the neurocognitive mechanisms of tDCS following SD, by comparing changes in the brain network, especially the thalamocortical network, after tDCS and sham stimulation following 24 h of SD. Sixteen healthy volunteers were tested in a sham-controlled, randomized crossover design experiment. Resting-state functional magnetic resonance imaging was conducted during resting wakefulness and again after either active tDCS or sham stimulation to the right dorsolateral prefrontal cortex (1.0 mA, 20 min) immediately following 24 h of SD. Seed-based correlations and graph theory analysis were used to determine functional connectivity within the brain thalamocortical network. When tDCS was used, the functional connectivity of the thalamus with the temporal lobe and left caudate was higher than that when the sham stimulation was used. Analysis using graph theory showed that compared with sham stimulation, tDCS administration was associated with a significant improvement in not only the number of connections but also the global efficiency of the thalamus itself. Our study reveals a modulation of the activity of the intrinsic thalamus networks after tDCS. The effects may help explain earlier reports of improvements in the cognitive performance after anodal-tDCS.